2014
DOI: 10.2320/matertrans.m2014071
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fluoride Anion on the Equilibrium between Titanium Ions and Electrodeposition of Titanium in Molten Fluoride–Chloride Salt

Abstract: NaClKClTiCl x was prepared via using titanium sponge to reduce titanium tetrachloride in a NaClKCl melt under a negative pressure at 1023 K. The relationship between titanium valence states and [F]/[Ti] molar ratios was investigated with successive adding potassium fluoride in the pre-prepared NaClKClTiCl x . It was found that the average valence of titanium ions tended to be stable around 3.0 when [F]/[Ti] molar ratio was greater than 1.80. The equilibrium redox potentials, E Ti 3þ =Ti 2þ , E Ti 4þ =Ti 3þ , E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…The electrodeposition of titanium metal has been studied in high-temperature molten salts. In previous studies, chloride melts [1][2][3][4][5] , uoride melts [6][7][8][9][10][11][12][13] , and mixed uoride-chloride melts [14][15][16][17] were investigated as electrolytes. In chloride melts such as LiCl-KCl 1) , NaCl-KCl 2) , CaCl 2 3) , and NaCl-CsCl 4) , the morphologies of the products were dendritic or rough surface.…”
Section: Introductionmentioning
confidence: 99%
“…The electrodeposition of titanium metal has been studied in high-temperature molten salts. In previous studies, chloride melts [1][2][3][4][5] , uoride melts [6][7][8][9][10][11][12][13] , and mixed uoride-chloride melts [14][15][16][17] were investigated as electrolytes. In chloride melts such as LiCl-KCl 1) , NaCl-KCl 2) , CaCl 2 3) , and NaCl-CsCl 4) , the morphologies of the products were dendritic or rough surface.…”
Section: Introductionmentioning
confidence: 99%
“…As the result, α 1 0 1 is higher than 1.8 for all the deposits, which demonstrates the high orientation to 101 plane. Oki et al reported that the Ti metal lm deposited on nickel in KCl-NaCl-LiCl containing K 2 TiF 6 at 923 K was highly orientated to 002 plane 17) . They also reported that the orientation varied with temperature, electrolysis time, current density, and electrolysis method.…”
Section: Galvanostatic Electrolysismentioning
confidence: 99%
“…The in uence of the addition of F − ions into chloride melts on the morphology of the Ti deposits has also been investigated. Song et al reported that the addition of KF into KCl-NaCl up to a molar ratio of [F − ]/[Ti n+ ] = 6 led to the deposition of Ti metal with ne crystal grains, which is advantageous for the formation of compact and smooth Ti lms 17) . According to Oki et al, Ti(II) ions were not formed during the electrochemical reduction when the added amount of KF in NaCl-KCl-3 mass% K 2 TiF 6 exceeded 10 mass% 18) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 This implies that [TiF 6 ] 2¹ is obtained through the reaction TiCl 4 with fluoride salt. Therefore, this study presented a direct electrolysis process for producing titanium from TiCl 4 in molten NaCl-KCl-NaF.…”
Section: ¹mentioning
confidence: 99%